Alih Kode dan Campur Kode pada Novel Septihan Karya Poppi Pertiwi - Desy Praditasari; Atiqa Sabardila (Universitas Muhammadiyah Jember, 2022)
This article aims to (1) analyze the contribution of code switching and code mixing studies in the analysis of intrinsic and extrinsic elements in the Septihan novel, (2) analyze the use of code switching studies in the Septihan novel, and (3) analyze the use of code mixing studies in the Septihan novel. This article uses a descriptive qualitative research method. The analytical technique used is a descriptive technique by describing the data obtained and then analyzing it. The data collection in this article uses library methods in the form of reading techniques, note-taking techniques, and data identification techniques. The findings obtained are (1) there is a form of code switching in Septihan novel, (2) there is a form of code mixing in the form of word insertion, phrase insertion, and baster insertion. (2) the contribution of the study of code switching and code mixing in the analysis of intrinsic and extrinsic elements in Septihan's novel. In this article, it is hoped that it will provide benefits and positive things for the general public.